2022
DOI: 10.7717/peerj.13727
|View full text |Cite
|
Sign up to set email alerts
|

Wide space sowing achieved high productivity and effective nitrogen use of irrigated wheat in South Shanxi, China

Abstract: Wheat (Triticum aestivum L.) is a staple crop worldwide, and its yield has improved since the green revolution, which was attributed to chemical nitrogen (N) fertilizer application. However, regular N application decreases N use efficiency (NUE, the ratio of grain dry matter yield to N supply from soil and fertilizer). Various practices have been implemented to maintain high crop yield and improve NUE. Nowadays, the enhanced sowing method, i.e., wide space sowing (WS), has improved the productivity of wheat cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…This benefitted the growth of tillers and roots and resulted in an efficient N absorption capacity during the whole wheat growing season (Lv et al, 2020). In the present study, WB markedly improved grain yield and NUE at N168, N240, and N312, due to the improved plant N uptake, in line with Wang et al (2022) and Zheng et al (2023). This may be related to the improved activity of N assimilation enzymes in WB sowing, because higher activities of N assimilation enzymes, such as nitrate reductase, nitrite reductase, glutamine synthetase, glutamate synthase, are beneficial for crop N assimilation and absorption (Chandna et al, 2012;Agnihotri and Seth, 2016;Gupta and Seth, 2019).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This benefitted the growth of tillers and roots and resulted in an efficient N absorption capacity during the whole wheat growing season (Lv et al, 2020). In the present study, WB markedly improved grain yield and NUE at N168, N240, and N312, due to the improved plant N uptake, in line with Wang et al (2022) and Zheng et al (2023). This may be related to the improved activity of N assimilation enzymes in WB sowing, because higher activities of N assimilation enzymes, such as nitrate reductase, nitrite reductase, glutamine synthetase, glutamate synthase, are beneficial for crop N assimilation and absorption (Chandna et al, 2012;Agnihotri and Seth, 2016;Gupta and Seth, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…This benefitted the growth of tillers and roots and resulted in an efficient N absorption capacity during the whole wheat growing season ( Lv et al., 2020 ). In the present study, WB markedly improved grain yield and NUE at N168, N240, and N312, due to the improved plant N uptake, in line with Wang et al. (2022) and Zheng et al.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, increasing the seed rate is applied to adapt wide-belt precision planting to compensate for the negative impacts of suboptimal land preparation and low soil fertility on the emergence rate and tillering capacity. For example, after this technique was introduced in Shanxi Province, China, the local farmers applied seed rates of 300-700 m −2 or even higher, and the yields increased by more than 10% [13]. Due to the higher seed rate, especially with suboptimal soil preparation, this sowing technique is referred to as wide-belt sowing (WBS).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the higher seed rate, especially with suboptimal soil preparation, this sowing technique is referred to as wide-belt sowing (WBS). Previous studies have demonstrated that the yield increases under WBS are due to increases in the tillering capacity, ears number, and leaf area index (LAI), and thus biomass production [13][14][15].…”
Section: Introductionmentioning
confidence: 99%